Interannual Variation in Area and Productivity of Crops as Influenced by Rainfall, Soil and Land Holding in Changeri Micro-watershed of Udaipur District of Rajasthan - Singh, Aditya Kumar; Singh, R S; Singh, S K; Shyampura, R L (Annals of Arid Zone, 2016)
Reasons for yield gap on the farms owned by medium to large farmers and marginal to small farmers have been investigated based on the socio-economic survey of 130 farm families and soil characteristics. Reasons for inter-annual variation in land use pattern from 2002 to 2004 were also studied simultaneously. Better soil conditions such as depth, texture, water holding capacity, slope and good management were the causes for 30 to 50% higher yield on the farms owned by medium to large farmers as compared to the farms belonging to marginal to small farmers. Food habits and dietary needs control the area for maize, whereas per capita return and lower water requirement influenced the area under groundnut, mustard and cumin. Sub-optimal rainfall sometimes led to increased area under sorghum at the cost of other kharif crops. Water available for irrigation, which is declining on account of depleting ground water resources, decided the area of wheat crop. Key words: Land holdings, constraints of production, soils, prices of crops, selection of crops.